The Development of Teaching Factory Module to increase The Interest in Entrepreneurship through Competency Based Training Model in Central Java State Vocational School - Rohman, Fatkur (Journal of Vocational and Career Education, 2020)
Vocational High School (SMK) is an educational institution at the secondary level which aims at preparing students to become competent and independent workforce by prioritizing abilities and skills in certain fields. The selection of appropriate learning media can increase interest in entrepreneurship significantly. The group taught using the developed module on SMAW arc welding showed significant difference compared to the group who did use the module. This study involved eleventh grade students at construction and property business focus in SMK Negeri Jawa Tengah in 2020/2021. This study aims to develop a module for the Shield Metal Arc Welding (SMAW) training by using teaching factory (TEFA) based on Competency - based Training (CBT). This training aims to increase the interest of students in entrepreneurship. The research used ADDIE research and development design. The ADDIE research design consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. The unit of analysis of this study is the module for Shield Metal Arc Welding (SMAW) training. Instruments used in research consisted of (1) assessment sheet of the module for Shield Metal Arc Welding (SMAW) training; (2) questionnaire of the practicality of the module for Shield Metal Arc Welding (SMAW) training; and (3) a questionnaire to measure the entrepreneurial interest of eleventh grade students at Property and Construction Business expertise and Mechanical Engineering in SMK Negeri Jawa Tengah. The data analysis used in this study consisted of (1) categorical to determine the feasibility level of the module for Shield Metal Arc Welding (SMAW) training; (2) Guttman categorical to determine the level of practicality level of the module for Shield Metal Arc Welding (SMAW) training, by using the Kr and Ks coefficient; and (3) N-Gain and the t – test for the N-Gain, to determine the effectivity of the on the entrepreneurship interests of students. The test of feasibility, practicality, and the effectivity of the module for Shield Metal Arc Welding (SMAW) training involved lecturers as the media expert, the head of Mechanical Engineering and The Teaching Factory Guide as learning material experts. The tests showed that the learning module was feasible, very practical, and sufficiently effective and could significantly increase the entrepreneurship interests of the eleventh-grade students at SMK N Jateng.